2021
DOI: 10.1038/s41380-021-01090-5
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of higher-order occipital GABA and impaired visual perception in acute major depressive disorder

Abstract: Major depressive disorder (MDD) is a complex state-dependent psychiatric illness for which biomarkers linking psychophysical, biochemical, and psychopathological changes remain yet elusive, though. Earlier studies demonstrate reduced GABA in lower-order occipital cortex in acute MDD leaving open its validity and significance for higher-order visual perception, though. The goal of our study is to fill that gap by combining psychophysical investigation of visual perception with measurement of GABA concentration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
46
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 39 publications
7
46
1
Order By: Relevance
“…Indeed, many lines of studies have reported that MDD is often associated with the subjective experience of altered visual perception, such as photophobia, perceived dimness and reduced visual contrast discrimination ( 49 51 ). Moreover, the impairment in visual perception was found to be directly related to the psychopathological symptoms of MDD ( 4 , 8 ). In our study, we found PPS, as indicated by amplitude ratios (A2s/A1), was significantly related to the symptom severity of depression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, many lines of studies have reported that MDD is often associated with the subjective experience of altered visual perception, such as photophobia, perceived dimness and reduced visual contrast discrimination ( 49 51 ). Moreover, the impairment in visual perception was found to be directly related to the psychopathological symptoms of MDD ( 4 , 8 ). In our study, we found PPS, as indicated by amplitude ratios (A2s/A1), was significantly related to the symptom severity of depression.…”
Section: Discussionmentioning
confidence: 99%
“…The psychophysical deficits in visual perception in MDD are closely related to the abnormality of biochemical changes in the occipital cortex. Using proton magnetic resonance spectroscopy, previous studies have consistently shown a decreased concentration of gamma-aminobutyric acid (GABA) in the visual cortex of MDD subjects (6)(7)(8), which can be normalized following effective therapeutic interventions (9)(10)(11). As an important inhibitory neurotransmitter, GABA was considered to mediate the centersurround suppression effect in visual perception (12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies that used the Paced Visual Serial Addition Test and Inspection Time Test found that depression patients had slower visual processing speeds and made more calculation errors compared to healthy controls 37,38 . Depression patients have also been shown to perform worse on visual processing tasks such as the Stroop Colour Word Test and in visual surround motion suppression 39,40 . Our demonstration of similar effects on cortical processing of apical (cortico-cortical inputs) and the canonical nature of the cortical microcircuitry 41 also generalize the implications of our results to higher-order deficits 42 , an important topic that can be explored carefully in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed that structural and functional abnormalities of the visual cortex may be related to the pathogenesis of depression. For example, gamma-aminobutyric acid (GABA) levels ( Kugaya et al., 2003 ; Price et al., 2009 ) and GABAergic neurons ( Maciag et al., 2010 ) are remarkably decreased in the occipital cortex of MDD patients, which may relate to abnormalities in visual perception and psychopathological symptoms ( Song et al., 2021 ). Compared with healthy controls, MDD patients exhibit reduced voxel-mirrored homotopic connectivity of the visual cortex, which is negatively associated with Hamilton Depression Rating Scale scores ( Deng et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%